Ultrasound-assisted extraction of total flavonoids from Aconitum gymnandrum - Zheng, Ling-Li (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Aconitum gymnandrum is a Chinese traditional herb used as carminative and analgesic. In this study, A. gymnandrum was used as an experimental matrix. MATERIALS AND METHODS: Optimized ultrasonic extraction technology of total flavonoids from the A. gymnandrum Maxim was studied by using the methodology of single factor and orthogonal design to study the effects of operation conditions, such as ethanol content, ultrasonic wave power, temperature, ultrasonic wave radiation time, and the ratio of sample weight to solvent volume. RESULT: Through the orthogonal experiment, the optimal extraction conditions were determined as follows: Ultrasonic power 100 W, ultrasonic temperature 45°C, 60% ethyl alcohol, extraction time 30 min, and solid–liquid ratio 1:20. CONCLUSION: Under the optimum parameters, the extraction ratio of total flavonoids from the A. gymnandrum Maxim is about 1.278%.